2019
DOI: 10.1017/wsc.2019.68
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidal properties of the commercial formulation of methyl cinnamate, a natural compound in the invasive silver wattle (Acacia dealbata)

Abstract: Plants that release molecules affecting other plants are a source of potential bioherbicides. Silver wattle (Acacia dealbata Link), considered invasive worldwide, was found to be phytotoxic to various other plant species. Combining the search for alternative bioherbicides while reducing the spread of this invader by preventing seed formation is a good potential strategy to solve both agricultural and environmental problems. This study aimed to identify nonvolatile compounds from A. dealbata flowers and explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 68 publications
(104 reference statements)
2
11
0
Order By: Relevance
“…Methyl cinnamate is a compound found in the flowers of A. dealbata and other plants (Khanh et al, 2008) and has shown its herbicidal effects on Lolium rigidum Gaudin with its application reducing guaiacol peroxidase activity up to 57% and also inhibiting early stem and radicle growth of L. rigidum by 76% and 87%, respectively (Lorenzo et al, 2020). Methyl cinnamate can also significantly reduce L. rigidum seed germination and root length when applied at 640 nL cm -3 (Vasilakoglou et al, 2013).…”
Section: Allelopathic Effects Of Acacia Dealbata Link On Weedsmentioning
confidence: 99%
“…Methyl cinnamate is a compound found in the flowers of A. dealbata and other plants (Khanh et al, 2008) and has shown its herbicidal effects on Lolium rigidum Gaudin with its application reducing guaiacol peroxidase activity up to 57% and also inhibiting early stem and radicle growth of L. rigidum by 76% and 87%, respectively (Lorenzo et al, 2020). Methyl cinnamate can also significantly reduce L. rigidum seed germination and root length when applied at 640 nL cm -3 (Vasilakoglou et al, 2013).…”
Section: Allelopathic Effects Of Acacia Dealbata Link On Weedsmentioning
confidence: 99%
“…The authors found methyl cinnamate as the most active compound, which showed selective phytotoxicity by inhibiting early stem and radicle growth of dicotyledonous lettuce (60% and 89%, respectively) and monocotyledonous L. rigidum (76% and 87%, respectively), but not affecting wheat. These results encouraged the exploitation of A. dealbata flowers as a source of potential bioherbicides, namely to be applied in wheat crops infested by rigid ryegrass [19]. A water extract from A. melanoxylon leaves evidenced promising results as a potential bioherbicide agent, given the inhibitory effect on the growth of Galician native species [64].…”
Section: Potential Bioherbicide Agents From Flowersmentioning
confidence: 97%
“…can be of great economic importance, since they are important sources of essences for the cosmetic and perfume industries and are of valuable anthochlor pigments (chalcones), in addition to relevant biological activities that have been found in their extracts. Moreover, its exploitation can be of crucial importance to the control of the propagation of Acacia spp., once its collection during the flowering period prevents the formation of seeds, so hindering plant proliferation through the seed dispersal route [19]. The biological activities and uses of Acacia spp.…”
Section: Flowersmentioning
confidence: 99%
See 2 more Smart Citations